El fuego - Rubín, David, 1977- (Oni Press, 2025)
"A mass-extinction event is imminent as a giant meteorite is hurtling toward the Earth. Renowned architect Alexander Yorba, entrusted to design a citadel on the Moon which would ensure the survival of humanity, is diagnosed with a terminal illness. Thrust into an existential crisis, Alexander begins to question the validity of his successes, having colluded with the world's elite to spare only the wealthiest members of society, and grapples with what it means to be a decent person in a decaying world. His spiritual and moral journey will take him from the Moon to Madrid, by way of New York, Helsinki, Amsterdam, and Rome, where he will have to confront his past choices with those who were his greatest influences, in hopes of finding his way . . . before the end comes"--